Analisis Pola Perjalanan Penumpang LRT di Palembang Menggunakan Metode K-Means Clustering Berdasarkan Data Gate dan Waktu Perjalanan - Rahman Ajie; Siti Sa’uda; Ahkmad Ipandy (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study analyzes travel patterns of Single Trip ticket users of the Light Rail Transit (LRT) in Palembang City using the K-Means Clustering method within the Knowledge Discovery in Databases (KDD) framework. The dataset comprises 9,377 Single Trip ticket transaction records from the BPKARSS ticketing system on August 6, 2025. Modeled attributes include origin station code (gate-in), destination station code (gate-out), departure time in decimal format, and estimated travel duration derived through feature engineering. The Elbow Method identified K=3 as the selected cluster count based on the inflection point of the WCSS curve, further supported by a Silhouette Score of 0.3044 (moderate category), indicating discernible but partially overlapping clusters. K-Means with K-Means++ initialization produced three passenger segments: Cluster 0: Short-Distance Travel Pattern (39.8%; n=3,735), Cluster 1: Medium-Distance Travel Pattern (29.0%; n=2,724), and Cluster 2: Long-Distance Travel Pattern (31.1%; n=2,918). The results indicate that all cluster centroids fall within the midday period (12:45–13:45 WIB), which differs from conventional peak-hour assumptions. These findings offer an empirical basis for consideration in operational policy formulation.